2019
DOI: 10.1007/s11676-019-00955-4
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground biomass allometric equations and distribution of carbon stocks of the African oak (Afzelia africana Sm.) in Burkina Faso

Abstract: The significant role of tropical forest ecosystems in the global carbon budget has increased the need for accurate estimates of tropical forest biomass. The lack of large-scale biomass allometric equations hampers the understanding of the spatial distribution of tree biomass and carbon stocks and their influencing factors in West Africa. This study aimed to develop allometric equations to estimate aboveground biomass of African oak (Afzelia africana Sm.) in Burkina Faso and to analyze factors affecting the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
7
11
2
Order By: Relevance
“…Branch contributed for approximately 64% of TAGB in the two climatic zones, whereas leaf represented the smallest portion (<3%) in both zone. These results are consistent with several published studies in the tropical African savanna species as Vitellaria paradoxa, Combretum glutunosum, Terminalia laxiflora and Afzelia africana ( Mensah et al., 2016 ; Balima et al., 2019 ; Dimobe et al., 2019 ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Branch contributed for approximately 64% of TAGB in the two climatic zones, whereas leaf represented the smallest portion (<3%) in both zone. These results are consistent with several published studies in the tropical African savanna species as Vitellaria paradoxa, Combretum glutunosum, Terminalia laxiflora and Afzelia africana ( Mensah et al., 2016 ; Balima et al., 2019 ; Dimobe et al., 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…This trend being observed at the components and tree levels between the two climatic zones, suggests that climate does not affect aboveground biomass distribution within B. aegyptiaca tree component, and the C content. Similar results were recently found by Balima et al. (2019) on Afzelia Africana, and these authors concluded that this might be related to a low climatic variation between two neighboring climatic zone as the case of our study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations